La enseñanza de las lenguas indígenas en Costa Rica - Carmen Rojas-Chaves (Revista Electrónica Educare)
In Costa Rica there are six indigenous languages which currently are becoming weaker due to the so-called “unified nation” with one language and one culture. Due to this situation, Costa Rica has ratified international agreements to conserve and spread autochthonous languages and cultures, along with promoting the education of indigenous children.